Impact of Cigarette Smoking on Re-operation and Revision Surgery after Femoral Neck Fracture Treatment - Messner, Mitchell; Chong, Alexander; Piatt, Bruce (Kansas Journal of Medicine, 2020)
Introduction. Smokers and nicotine users have a higher risk of femoral neck fracture non-union and prolonged time to fracture union. The impact of smoking resulting in revision surgery after fixation of femoral neck fractures, however, rarely has been studied. The aim of this retrospective study was to review if cigarette smoking had an influence on re-operation and revision after femoral neck fracture treatment. Methods. Three groups of patients (Group 1: active smokers; Group 2: former smokers; and Group 3: non-smokers) who sustained a femoral neck fracture from January 2012 through August 2018 were included. Outcomes investigated included femoral neck fracture type, operative fixation type, fixation failure, and time interval between initial fixation and revision. Results. A total of 1,452 subjects were identified (Group 1: 165 subjects; Group 2: 507 subjects; and Group 3: 780 subjects). In the male population, Groups 1 and 2 had higher rates of femoral neck fracture than Group 3. Twelve cases required revisions (Group 1: three cases (6%); Group 2: two cases (2%); Group 3: seven cases (4%)), with all but one revision within the first year following initial fixation. Group 1 patients tended to be younger than the other two groups. Conclusion. Smoking has a positive association with the risk of femoral neck fracture amongst active and former male smokers. This study concluded that active smokers have a higher risk of non-union compared with non-smokers or former smokers. Smoking history, especially heavy or long-term, should play a role in deciding which fixation construct type to use for femoral neck fractures.